ANALYSIS OF POST-PANDEMIC TOURISM DEVELOPMENT BASED ON RESOURCE MANAGEMENT OF INDONESIAN CREATIVE BUSINESS - Winduwati, Septia; Saraswati, Kiky D.H.; Putri, Cahaya R. (ASPIRATION Journal, 2025)
The COVID-19 pandemic has significantly impacted tourism in Indonesia, causing a sharp decline in both foreign and domestic visitors and leading to decreased income for tourism businesses such as hotels, restaurants, and tour guides. Although the vaccination program and government stimulus policies, including tax reductions, have supported gradual recovery, the sector still faces serious challenges such as low tourist arrivals, difficulty in maintaining health protocols, limited capital, dependency on foreign tourists, and inadequate infrastructure. In this context, communication science and industrial psychology play a crucial role in shaping effective communication strategies, human resource management, service innovation, performance measurement, and reputation management to strengthen resilience in post-pandemic tourism. This study contributes to theory development by integrating concepts of Customer Relationship Management (CRM), service innovation behavior, and creative economy theory into the framework of tourism recovery. By doing so, it enriches theoretical discussions on how communication and resource management can drive competitiveness and sustainable value creation in the tourism sector. Practically, the findings highlight that effective CRM implementation through meaningful communication, personalization techniques, and lifecycle management that enhances trust, customer satisfaction, loyalty, and positive word-of-mouth. These insights provide actionable strategies for tourism practitioners to rebuild relationships with customers, maintain long-term engagement, and adapt to post-crisis market dynamics. This qualitative descriptive research involved purposive sampling of tour guides and tourism entrepreneurs in Bali—one of the destinations most affected by the pandemic. Data were collected through in-depth interviews, field observations, and document studies, then analyzed using thematic analysis. To ensure validity and reliability, the study employed triangulation of data sources and member checking. The results demonstrate that CRM is not only an operational tool but also a strategic approach that links theory with practice, offering both academic contributions and practical pathways for strengthening the competitiveness of Indonesian tourism in the post-pandemic era.